Identifying suitable land for dust storm barriers in Al-Anbar region using GIS - Hussein, Aseel M.; Emami, Alireza; Fattah, Mohammed Y.; Abdullahi, Saleh (Brawijaya University, 2026)
This study employed an integrated Geographic Information System (GIS) and Analytic Hierarchy Process (AHP) methodology to identify optimal locations for sand and dust storm barriers in Iraq’s Al-Anbar Governorate. Six critical spatial and environmental criteria were analyzed: dust storm frequency, proximity to residential areas, wind speed and direction, soil pH, moisture content (NDWI), and vegetation cover (SAVI). The AHP framework assigned weighted importance to these factors, with residential proximity (38.1%) and storm frequency (25.1%) being the most significant. The results classify the study area into three suitability tiers: high (7%, 9,695 km²), moderate (28%), and low (65%). High-suitability zones are predominantly located near settlements (at an average distance of 1.2 km) in the path of northeastern to southwestern winds and experience high dust storm frequency. This research provides a robust, data-driven framework for prioritizing dust storm mitigation efforts, enabling efficient resource allocation to protect communities and enhance environmental sustainability in arid regions.